Design, Synthesis, and Biological Evaluation of Multitargeted N-Benzylpiperidine Analogs for the Treatment of Alzheimer’s Disease - Sharma, Piyoosh (IIT BHU VARANASI, 2019)
Abstract is available in content
Keywords: Design, Synthesis, and Biological Evaluation; of Multitargeted N-Benzylpiperidine Analogs; for the Treatment of Alzheimer’s Disease